Ancient Information on Persia Re-assessed : Proceedings of a Conference Held at Marburg in Honour of Christopher J. Tuplin, December 1-2, 2017 - Jacobs, Bruno (Classica et Orientalia, 2020)
Cover -- Title Pages -- Contents -- Foreword -- Introduction -- Bruno Jacobs: Christopher J. Tuplin: an Appreciation -- Bibliography of Publications of Christopher J. Tuplin -- Genre and Meaning -- Frances Pownall: Xenophon's Cyropaedia and Greek Historiography -- Irene Madreiter: Cyropaedia and the Greek 'Novel' again -- Louis-André Dorion: Cyrus and Socrates: Two Models on an Equal Footing? -- The Author's View -- Reinhold Bichler: Cyropaedia - 'Historical Space' and the Nations at the Fringes of the Oikumene -- John E. Esposito: On the Fundamental Activities of the Leader in Xenophon's Education of Cyrus -- Michael A. Flower: Xenophon's Anabasis and Cyropaedia: a Tale of Two Cyruses -- Gabriel Danzig: The Younger Cyrus and the Alter Cyrus -- Cyropaedia as Historical Source -- Julian Degen: Ancient Near Eastern Traditions in Xenophon's Cyropaedia -- Bruno Jacobs: Cyropaedia and the "Gift-Bearer Reliefs" from the So-called apadāna at Persepolis -- Literary Reception -- Sabine Müller: Xenophon's Kyroupaideia and the Alexander Historiographers -- Deborah L. Gera: Luxury and Authority in the Cyropaedia, Esther, and Judith -- Sulochana Asirvatham: The Cyropaedia in Imperial Greek Literature -- Richard Stoneman: Xenophon's Education of Cyrusin Early Modern Europe -- Noreen Humble: Worn out in the Reading: Xenophon's Cyropaedia in the Sixteenth Century -- Melina Tamiolaki: Straussian Readings of the Cyropaedia: Challenges and Controversies -- Concluding Remarks -- Vivienne Gray: Reflections on Near Eastern Realities in the Cyropaedia -- Indices -- Names of Persons and Deities -- Topo- and Ethnonyms.